Passive Antenna Systems Embedded into a Load Bearing Wall for Improved Radio Transparency - Vähä-Savo, Lauri; Atienza, Alejandra Garrido; Cziezerski, Christian; Heino, Mikko; Haneda, Katsuyuki; Icheln, Clemens; Lu, Xiaoshu; Viljanen, Klaus (IEEE, 2021)
Providing cellular network services inside residential or office buildings has become challenging, especially for fifth-generation networks that use higher carrier frequencies. Additionally, new energy-efficient buildings contain envelopes such as low-emissivity glass and new multi-layer thermal insulations, all of which - unintendedly but effectively - also block radio signals. As a solution to those problems of indoor coverage, we suggest the use of passive antenna systems embedded into the building walls. We propose a numerical evaluation method for determining the electromagnetic transmission coefficient and the thermal insulation of a typical building wall. Next, we investigate two antenna configurations embedded to the wall, a two-patch and a four-patch design, both operating around 3.5 GHz. We show from numerical simulations that those antenna systems increase the transmission coefficient of the wall. At the same time, we show that the four-patch design does not compromise the thermal insulation of the wall.
Keywords: Antenna systems; energy efficient buildings; radio transparency; thermal transmittance; fi=Energiatekniikka|en=Energy Technology|